Quick analysis of composition of semi-aromatic copolyamide via 13C NMR study. Issue 1 (2nd January 2019) - Zhang, Chuanhui; Cao, Min; Jiang, Sujun; Huang, Xianbo; Mai, Kancheng; Yan, Kun
Abstract: Standard high resolution 13 C NMR spectra of PA10T, PA6T, PA106, and PA66 were obtained by a nonacidic solvent mixture of HFIP and CDCl3 . Several chemical shifts were found extremely sensitive to the polyamide type. According to the standard spectra, semi-aromatic copolyamides comprising PA10T, PA6T, PA106, and PA66 units could be distinguished. The ratio of each polyamide component in the copolyamide was determined through the integration of the methylene carbon peak associated with the amine group. 13 C NMR analysis results were consistent with the theoretical values and copolyamide hydrolysis test results, making 13 C NMR analysis quite reliable on the quick composition analysis of semi-aromatic copolyamides. Based on this technique, several commercial semi-aromatic copolyamides were further examined and their compositions were easily determined.